Role of Extracellular Vesicles on Cancer Lymphangiogenesis and Lymph Node Metastasis - Wang, Linlin; Li, Ling; Zhu, Guiquan (Frontiers in Oncology, 2021)
Lymph node metastasis (LNM) of tumors is an established indicator of poor prognosis in patients. Tumor-associated lymphangiogenesis is a key step in LNM and has gained much attention. However, currently, there is no anti-tumor lymphangiogenesis drug used in clinical practice. Recently, studies on extracellular vesicles (EVs) have shown that different types of cells in the tumor microenvironment can release EVs that encapsulate a variety of molecules, including proteins, nucleic acids, and metabolites. Lymph endothelial cells (LECs) regulate tumor lymphangiogenesis through the uptake of EVs packed with different biologically active contents. In this review, we will discuss the possible mechanisms by which EVs participate in the regulation of tumor-associated lymphangiogenesis and LNM, summarize the potential value of EVs that can be used as biomarkers for the determination of tumor LNM, and indicate the potential anti-tumor lymphangiogenesis therapy.